Deviations from interest rate parity in small open economies: A quantitative-theoretical investigation - Lorand Ambrus-Lakatos; Balazs Vilagi; Janos Vincze (Hungarian Academy of Sciences, Institute of Economics, 2004)
It is frequently claimed that the expected yield on emerging market bonds commands a premium. Here we investigate the sources of this phe-nomenon. A stochastic general equilibrium model of a small open economy is analyzed numerically to derive conditions for interest rate premia. The novelty of our approach is to attack the problem form the point of view of state dependent policy mixes. The main lessons include: if positive premia were universal, then 1. nominal rigidity should be important, 2. monetary authorities might have a current account stabilization motive, and 3. taste shocks possibly play some role in emerging markets.
Keywords: 330